O61 Development of a registrar to consultant transitional training course. (5th November 2017) - Walker, T; Humphreys, A; Tasker, A; Shabbir, J; Coulston, J
Abstract : Introduction: Transitioning through levels of surgical training is highly stressful and these periods can be error prone. The Severn School of Surgery runs transitional training "bootcamps" for core and specialty level surgical trainees. There are no free training courses available nationally that provide human factors and non-technical skills training for surgeons making the transition between registrar and consultant. We present the structure, learning objectives and impact on trainee confidence levels of a course developed that aims to to aid this transition. Methods: The course was split over two days and delivered by an expert multidisciplinary faculty: the first day focused on human factors training with seminars and immersive simulation scenarios, the second day introduced wider relevant topics such as medico-legal perspectives, NHS culture, how to deal with complaints, bullying and harassment as well as a workshop on leadership and management. Confidence questionnaires pre- and post- bootcamp were provided with a 1–10 likert scale. Feedback forms for each session were completed with agreement ratings 1(strongly disagree)−5 (strongly agree). Data were analysed using t-tests with level of significance set at p<0.05. Agreement data were reported as the weighted average score for each question. Results: Twenty delegates attended the 'bootcamp' over two days. There were delegate representatives from the surgical specialities of colorectal, breast, upper gastro-intestinal, hepatobiliary, trauma and orthopaedics, ophthalmology, ENT and cardiothoracics. There were significant increases in candidate's confidence levels performing as a consultant with regard to: overall confidence (p=0.008), non-technical skills (p=0.042), leadership (p=0.045), conflict communication (p=0.012), NHS structure (p=0.01) and NHS management (p=0.002). Feedback was overwhelmingly positive: candidates agreed strongly with the relevance of the chosen curriculum (4.51), felt strongly that they had knowledge acquisition (4.52), felt more prepared to be a consultant (4.53) and enjoyed the course (4.56). Discussion: This course, free for delegates and available to multiple surgical specialties within the South West, aims to aid the transition between registrar and consultant life. Positive feedback was achieved during this first year. Confidence levels amongst candidates significantly improved over the duration of the course especially in the domains of conflict resolution, NHS structure and NHS management.